Foreign Direct Investment in Latin America and the Caribbean 2019 - United Nations (United Nations, 2019)
This ECLAC annual report sets out and analyses the main foreign direct investment (FDI) trends in the countries of Latin America and the Caribbean. In the region, FDI inflows were up (by 13.2%) year on year for the first time in five years, at US 184.287 billion. This performance is explained by higher flows into just a few countries, however, mainly Brazil and Mexico. Moreover, it does not reflect equity investment, but higher inflows in the form of intercompany loans and, to a lesser extent, reinvestment of earnings. Manufactures and services were the sectors receiving most equity, although there was a slight rise in investment in natural resource sectors compared with 2018.